Trends in United States Drug Shortages for Medications Used in Gastroenterology. Issue 1 (2017) - Patel, Jigar M.; Fox, Erin R.; Zocchi, Mark; Lee, Zone-En; Mazer-Amirshahi, Maryann
Introduction: Drug shortages have become more severe in recent years; however, data describing how such shortages impact gastroenterology (GI) drugs are limited. We characterize longitudinal trends of drug shortages in the USA within the scope of GI practice. Methods: Drug shortage data from the University of Utah Drug Information Service were analyzed from January 2001 to December 2014. A board certified gastroenterologist, an internal medicine physician, and a clinical pharmacist identified drug shortages within the scope of GI practice, whether they are used for high-acuity conditions, availability, formulation, or therapeutic category. Trends in the length of shortages for GI drugs were described using standard descriptive statistics and regression analysis. Results: A total of 1, 774 drug shortages were reported over the 14-year period. Of those, 253 shortages (14.3%) were classified within the scope of GI practice. The number of newly-reported GI drug shortages increased from 15 in 2001 to 44 in 2014. The majority of GI drugs (55.7%) were parenteral and 102 shortages (40.3%) were single source drugs. By the end of the study period, 44 (17.4%) GI drugs remained on active shortage with a median duration of 24.3 months (interquartile range [IQR] 6.9–32.1). The median duration for resolved shortages of GI drugs was 7.7 months (IQR 2.9–17.6). Conclusions: There was a significant increase in shortages of drugs used in GI practice from 2001 to 2014. Many of these drugs were used for high-acuity conditions and alternative agents were also impacted. Gastroenterologists must be cognizant of current shortages in order to mitigate impact on patient care.